Determinants of company innovation and market performance. Issue 1 (8th January 2018) - Psomas, Evangelos; Kafetzopoulos, Dimitrios; Gotzamani, Katerina
Abstract : Purpose: The present study focuses on two basic determinants of company innovation, namely, quality practices of top management and process quality management. The purpose of this paper is to explore the impact of these determinants on product and process innovation. Determining the impact of these dimensions of innovation on the market performance of a company is also an aim of the present study. Design/methodology/approach: A research study was carried out on a sample of 433 Greek manufacturing and service companies. Data were obtained through a structured questionnaire from the chief executive officers of the companies. Exploratory and confirmatory factor analyses are applied to extract and validate all the latent factors considered in the suggested model, while their relationships are determined through structural equation modeling. Findings: The analysis of the empirical data shows that both the dimensions of company innovation examined in the present study (product and process innovation) are positively influenced by the quality practices of top management and process quality management. Improving these two dimensions of company innovation, in turn, results in increased market performance. Research limitations/implications: First, the sample of the responding manufacturing and service Greek companies which includes both small and medium-sized enterprises and large companies and which operate in circumstances of financial crisis; second, the subjective data collected from only one company representative; and third, the examination of only two factors influencing company innovation, are the main limitations of the present study. Based on these limitations, future research studies are recommended. Practical implications: The empirically validated theoretical model of the present study can guide the policy makers of a company to select a quality management and innovation strategy through which the company can lay the foundations to increase its market performance, and thus, overcome the current economic downturn and financial crisis. Researchers can also use the suggested valid model as an assessment tool, a benchmarking tool and a tool for the design of their future research studies. Originality/value: The present study contributes to the literature by determining a valid model that describes simultaneously the relationships between quality management factors, product and process innovation and market performance. This is also the first study reflecting Greek companies' efforts to withstand the current downturn and penetrate the market through innovation.